Defining endoscopic response and remission in ulcerative colitis clinical trials: an international consensus. Issue 6 (23rd January 2017) - Vuitton, L.; Peyrin‐Biroulet, L.; Colombel, J. F.; Pariente, B.; Pineton de Chambrun, G.; Walsh, A. J.; Panes, J.; Travis, S. P. L.; Mary, J. Y.; Marteau, P.
Summary: Background: Recently, endpoints for clinical trials have been changing from measuring clinical response to mucosal healing in ulcerative colitis. Endoscopic evaluation is the current gold standard to assess mucosal lesions and has become a major measure of therapeutic efficacy in addition to patients reported outcomes. Aim: To achieve consensus on endoscopic definitions of remission and response for clinical trials in patients with ulcerative colitis. Methods: In reaching the current international recommendations on an International Organization For the Study of Inflammatory Bowel Disease (IOIBD) initiative, we first performed a systematic review of technical aspects of endoscopic scoring systems. Then, to achieve consensus on endoscopic definitions of remission and response for clinical trials, we conducted a two‐round vote using a Delphi‐style process among fifteen specialists in the field of inflammatory bowel diseases. Results: The literature review showed that many endoscopic indices have been proposed to evaluate disease activity in ulcerative colitis; most are unvalidated and arbitrary definitions have been used in clinical trials for defining endoscopic response or remission. At the end of the voting process, the investigators ranked initially the Ulcerative Colitis Endoscopic Index of Severity (UCEIS) 0 for the definition of endoscopic remission, and a decrease in Mayo endoscopic score ≥1 grade or a decrease in UCEIS ≥2 points for the definition of endoscopic response in ulcerative colitis. Conclusions: These international recommendations represent the first consensus on measurement indices for endoscopic outcomes in ulcerative colitis. They should be subject to prospective testing in clinical trials of ulcerative colitis. Abstract : Linked Content This article is linked to Christensen and Sparrow papers. To view these articles visithttps://doi.org/10.1111/apt.14007 .